An Observational Study on the Early Stages of the Covid-19 Pandemic in Pakistan - Mehreen Nasir, Muntazir Mehdi, Muhammad Waseem Qureshi, Anum Rahim, Shakeeb Tahir, Irum Shahzadi Awan (Pakistan Journal of Medical & Health Sciences, 2023)
Bachground: The coronavirus disease 2019 (COVID-19) pandemic, which started on February 26, 2020 in city of karachi, spread quickly throughout Pakistan. Material and Method: The design of this study was a observational study design and this study was conducted at king Edward medical University Lahore. More than 6,200 persons were afflicted by the illness in the first seven weeks, and there were more than 111 documented fatalities. Many problems arise if we contrast the COVID-19 tragedies in Pakistan with those in nations like China, Iran, and the European Union. The geography of the nation, poverty, poor literacy rates, environmental circumstances, sanitary conditions, and dietary habits are only a few of the difficulties we face in containing this epidemic. Although there are terrible circumstances in each of these areas, Pakistan’s COVID-19 epidemic was slower than that of other developing nations. Results: The impact of COVID-19 appears to be lessened by Pakistan’s humid hot temperature, early reaction to COVID-19, population immune system, BCG vaccination, and the proportion of young individuals. In this essay, we explore the COVID-19 pandemic outbreak in China, Iran, and Pakistan and present its day-to-day changes. We outline the COVID-19 structure and how it compares to SARS-COV and SARS-COV2. The use of Remdesivir (an adenosine analogue used against RNA viruses), Chloroquine (a widely used anti-malarial drug), convalescent plasma, neutralising antibodies targeting the ACE-2 receptor, and an ACE-2-like molecule that might bind to the S protein of the coronavirus are also covered in terms of treatment options and their drawbacks. Also covered are the effects of COVID-19 on Pakistan’s economy and government relief measures. Conclusion: In conclusion, it may be said that the support systems in place may not be sufficient to stop the spread of the virus. Even with the meagre assistance offered, it is weaker for rural places where the virus’s effects may be severe than in the nation’s cities. Further research is required as the epidemic develops to better understand governmental efforts to contain the virus and its effects across the nation. Keywords: Coronavirus COVID-19 Pakistan Pandemic Outbreak